Impact of corporate culture on the application of lean manufacturing in enterprises - Lan, Do Thi Ngoc; Yen, Nguyen Thi Hai; Ha, Thai Van; Thanh, Doan Tat (Edelweiss Applied Science and Technology, 2025)
The plastics industry is witnessing dramatic changes, technological breakthroughs, lean manufacturing processes, and new environmental regulations. Along with that is the constant adaptation of plastics firms to keep up with market trends and maintain competitiveness. The purpose of this study is to assess the factors affecting the application of lean manufacturing in supporting industrial production enterprises in Northern Vietnam: A Case Study of a Group of Plastic Molding Enterprises. The study uses a mixed-methods approach, surveying 82 plastic molding enterprises that have been applying Lean Manufacturing models. The analysis results show that three main factors affect the effectiveness of Lean application: (i) human resources (including employee competence, skills, and improvement awareness); (ii) leadership commitment (expressed through resource investment, policy issuance, and direct involvement in Lean deployment); and (iii) corporate culture (a working environment that encourages creativity, continuous improvement, and teamwork spirit). The study also provides insights into the application process of Lean in the production context of supporting industrial production enterprises. The practical implication of this study is lessons for other businesses in the industry.